NOTIONS OF CULTURE, CROSS-CULTURAL AWARENESS AND INTERCULTURAL COMPETENCE - Qodirov Xalilullo Raxmatullo o’g’li; Nosirjonova Shahzodaxon Kamoliddin Qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
In a world that is increasingly interconnected, cross-cultural awareness and intercultural competence have become essential for effective communication and collaboration across cultural boundaries. This article explores the notions of culture, cross-cultural awareness, and intercultural competence and demonstrates their importance in intercultural interactions. The article highlights the critical role of culture in shaping human behaviour, attitudes, preferences, and beliefs. It further discusses the importance of cross-cultural awareness in recognizing and appreciating cultural differences and similarities. The article presents intercultural competence as the ability to effectively communicate and interact with people from different cultures, and it emphasizes the need for individuals to adapt their communication style to fit cultural norms, recognize cultural differences and navigate them appropriately. The article concludes by highlighting the advantages of developing intercultural competence in the globalized world.